2022
DOI: 10.3390/su14148774
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Teaching with Technology after the Quarantine: Evidence from Chinese EFL Teachers’ Technological, Pedagogical and Content Knowledge

Abstract: Given that little is known about English teachers’ technological, pedagogical and content knowledge (TPACK), this study examined teachers’ TPACK of using interactive whiteboards (IWBs) by contextualizing the research in the Chinese EFL context. Surveys and multi-case interviews were conducted among secondary school EFL teachers. The results revealed that Chinese EFL teachers generally perceived themselves to be competent in TPACK, with content knowledge achieving the highest value (5.545) and technological kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
9
1
Order By: Relevance
“…Teachers considered themselves as being deficient, especially in technology-related knowledge and skills, and become online teaching marginal persons (Jin, 2021). These findings echo previous studies (e.g., Huang et al, 2022) that suggested English teachers perceived themselves as competent in the content and pedagogical knowledge, but incompetent in technology-related knowledge and skills, especially the technological, pedagogical, and content knowledge (TPACK). Fortunately, teachers became TPACK learners and managed to conduct ERT by adopting effective coping strategies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Teachers considered themselves as being deficient, especially in technology-related knowledge and skills, and become online teaching marginal persons (Jin, 2021). These findings echo previous studies (e.g., Huang et al, 2022) that suggested English teachers perceived themselves as competent in the content and pedagogical knowledge, but incompetent in technology-related knowledge and skills, especially the technological, pedagogical, and content knowledge (TPACK). Fortunately, teachers became TPACK learners and managed to conduct ERT by adopting effective coping strategies.…”
Section: Discussionsupporting
confidence: 89%
“…The technology integration has escalated to a higher level, which put forward a new requirement for teachers’ technological, pedagogical, and content Knowledge (TPACK). Previous studies show that English teachers’ attitudes toward technology use in teaching change in terms of their gender, academic major, years of teaching with technology, and TPACK ( Arcueno et al, 2021 ; Huang et al, 2022 ). It’s also indicated that the digital native teachers who have been well-educated in using technology or accustomed to using technology ( Prensky, 2001 ) show more positive attitudes than the others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the interview, it is found that teachers were very busy and had heavy workloads every day. Their time was occupied with classes from morning to night, in addition, they were tired from diverse non-teaching related tasks (Huang et al, 2022).…”
Section: Gordian Knot In Teaching Adaptationmentioning
confidence: 99%
“…With the rapid development of society and the continuous advancement of educational reform, people have paid increasing attention to teachers' professional development. Teachers' professional development runs through preservice training, in-service training, and continuing professional development, which provide opportunities for teachers to obtain sufficient knowledge and skills, including content, pedagogical, and technological knowledge and skills (Huang et al, 2022;Lai et al, 2022). In this process, teachers formed teaching beliefs and improved professional qualities and abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the network structure is constantly changing rather than stationary. The difficulty in the study of evolutionary networks is how to obtain unknown information [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%